2013
DOI: 10.1128/iai.00550-13
|View full text |Cite
|
Sign up to set email alerts
|

Emetic Potentials of Newly Identified Staphylococcal Enterotoxin-Like Toxins

Abstract: g Staphylococcal enterotoxins (SEs) are a common causative agent of food poisoning. Recently, many new SE-like (SEl) toxins have been reported, although the role of SEls in food poisoning remains unclear. In this study, the emetic potentials of SElK, SElL, SElM, SElN, SElO, SElP, and SElQ were assessed using a monkey-feeding assay. All the SEls that were tested induced emetic reactions in monkeys at a dose of 100 g/kg, although the numbers of affected monkeys were significantly smaller than the numbers that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 35 publications
5
79
1
4
Order By: Relevance
“…In 2013, Omoe et al confirmed in a primate model the emetic potential of SElK, SElL, SElM, SElN, SElO, SElP, and SElQ (13).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…In 2013, Omoe et al confirmed in a primate model the emetic potential of SElK, SElL, SElM, SElN, SElO, SElP, and SElQ (13).…”
Section: Resultsmentioning
confidence: 86%
“…A recent study confirmed the emetic potential of SElK, SElL, SElM, SElN, SElO, SElP, and SElQ in monkeys (cynomolgus monkeys) and proposed renaming them as SEK, SEL, SEM, SEN, SEO, SEP, and SEQ, respectively (13).…”
Section: Introductionmentioning
confidence: 74%
“…Uważa się, że najwyższą wrażliwością charakteryzuje się człowiek (6). Obecnie do badań wykorzystuje się małpy Macaca fascicularis oraz ryjówka domowego (Suncus murinus), ssaka należącego do rodziny ryjówkowatych (15,28). Wykorzystywanie małp wiąże się z wysokimi kosztami i pociąga za sobą wątpliwości natury etycznej.…”
Section: Aktywność Wymiotna Enterotoksyn Gronkowcowychunclassified
“…W eksperymentach przeprowadzonych na małpach, przy doustnym lub dootrzewnowym podaniu enterotoksyn A, B, C 2 , D oraz E ustalono, że do wywołania efektu wymiotnego konieczne jest podanie zwierzęciu od 5 do 20 µg enterotoksyny (6). Badania przeprowadzone dotychczas wskazują, że aktywność wymiotna enterotoksyn klasycznych jest nawet 2-krotnie wyższa niż nowo opisanych czynników (28). Prace przeprowadzone przez Hu i wsp.…”
Section: Aktywność Wymiotna Enterotoksyn Gronkowcowychunclassified
See 1 more Smart Citation